PERAN UMKM (USAHA MIKRO, KECIL, DAN MENENGAH) DALAM PEREKONOMIAN INDONESIA - Syaakir Sofyan (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
UMKM is a mandate of UUD 1945 which must be realized throughnational development based on economic democracy. UMKM have animportant role in addressing various issues and economic problems ofthe country, including the fulfillment of community needs forgoods/services, unemployment, and employment. In carrying out itsrole, UMKM still have many difficulties and limitations and have notbeen able to realize its ability and role maximally in social andeconomic function. The solution is the full involvement of thegovernment as policy makers, the banking industry as credit providersand the public. All three parties must synergize and play an active rolein realizing independent UMKM.